2017
DOI: 10.18632/oncotarget.19003
|View full text |Cite
|
Sign up to set email alerts
|

The neglected avian hepatotropic virus induces acute and chronic hepatitis in ducks: an alternative model for hepatology

Abstract: Duck Hepatitis A Virus (DHAV) belongs to the Avihepatovirus, which is also classified into Picornaviridae with Hepatovirus, Hepatitis A Virus (HAV). In humans, the pathogenesis of HAV is not well understood because of limited work with animal models. Here, we investigated the progress of duck viral hepatitis caused by DHAV and their potential for dissecting the pathogenesis of HAV. During the course of infection, the duck model had undergone hepatocellular lesions (vacuolation, acidophilic degeneration and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 49 publications
(58 reference statements)
3
23
0
Order By: Relevance
“…Furthermore, the liver surface exhibited extensive punctate hemorrhaging, and the liver parenchyma was significantly infiltrated with numerous red blood cells, accompanied by steatosis and necrosis. Similar effects were not observed in CH60-inoculated ducklings, but cytokine storms have been identified in the adult duck kidney 14 and liver 46 . Therefore, the pathological mechanisms induced by DHAV-1 are likely related to severe cytokine storms.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the liver surface exhibited extensive punctate hemorrhaging, and the liver parenchyma was significantly infiltrated with numerous red blood cells, accompanied by steatosis and necrosis. Similar effects were not observed in CH60-inoculated ducklings, but cytokine storms have been identified in the adult duck kidney 14 and liver 46 . Therefore, the pathological mechanisms induced by DHAV-1 are likely related to severe cytokine storms.…”
Section: Discussionsupporting
confidence: 54%
“…In coxsackievirus B3 (CVB3) infection, the 3C protease cleaves TRIF and mitochondrial antiviral signaling protein (MAVS) to suppress host immunity [33]. In DHAV infection, it has been reported that activation of the toll-like receptor 7 (TLR7) pathway is involved in the immune response and viral clearance [34]. To date, some epidemiological, pathogenic and immunological mechanisms of DHAV have been reported [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The mature ducks in this study were asymptomatic without significantly elevated serum bilirubin, but with elevations of serum alanine aminotransferase (ALT) activity as described previously ( 8 ). This permitted us to study features of asymptomatic hepatitis.…”
Section: Resultsmentioning
confidence: 99%
“…From 140 dpi, the viral copies declined again and finally became undetectable from 224 dpi onward. Hepatitis was first detectable as significantly elevated serum ALT activity at 28 dpi ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation